1976
DOI: 10.1901/jaba.1976.9-527
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Criterion Design

Abstract: This article describes and illustrates with two case studies a relatively novel form of the multiple-baseline design called the changing criterion design. It also presents the design's formal requirements, and suggests target behaviors and circumstances for which the design might be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
0
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(114 citation statements)
references
References 11 publications
0
113
0
1
Order By: Relevance
“…Although such a tool could help to ease application of the technique, the method is sufficiently complicated that if prompting and contingent reinforcement are adequate in establishing the response and consistency in technique across therapists is not of interest, a percentile schedule of reinforcement would not be recommended. Other control techniques, such as a changing criterion design (Hartmann & Hall, 1976), may be more suitable for use with shaping in such circumstances. The percentile method, however, offers sufficient benefits under certain conditions that its consideration as a therapeutic intervention and further research into the generality of its application are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although such a tool could help to ease application of the technique, the method is sufficiently complicated that if prompting and contingent reinforcement are adequate in establishing the response and consistency in technique across therapists is not of interest, a percentile schedule of reinforcement would not be recommended. Other control techniques, such as a changing criterion design (Hartmann & Hall, 1976), may be more suitable for use with shaping in such circumstances. The percentile method, however, offers sufficient benefits under certain conditions that its consideration as a therapeutic intervention and further research into the generality of its application are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies containing a CCD were identified through a search of PsycINFO, ERIC, and PubMed databases using the key word changing criterion as well as articles referencing Hartmann and Hall (1976). The introduction and discussion section of each article was examined to locate other studies utilizing a CCD.…”
Section: Methodsmentioning
confidence: 99%
“…A few subsequent studies utilized this design (i.e., Brown et al 1974;Wallace and Davis 1974) prior to the seminal article by Hartmann and Hall (1976), which described the CCD in more detail and noted its similarity to a procedural description by Sidman (1960, pp. 254-256) in reference to the evaluation of irreversible behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The changing criterion design is also relevant to optimizing interventions [34]. In a changing criterion design, a baseline is conducted until stability is attained.…”
Section: Changing Criterion Designmentioning
confidence: 99%